Women Reflect on Being Well in Academia: Challenges and Supports (LEARNing Landscapes, 2017)
A narrative approach was adopted to explore the experiences of 13 women who pursued academic careers. Analysis of the personal reflective narratives uncovered themes common to the participants, also the authors of this study, which focused on striving to have work-life balance, personal and professional costs associated with being unwell, and the impact of academic work on families. Findings highlighted suggestions for being well in academia such as choose to engage in work and leisure activities that are enjoyable and maintain relationships. Suggestions for universities included: provide clear promotion and tenure processes, examine workload expectations, promote wellness, and facilitate mentorship.About Memorial University’s Faculty of Education Writing GroupIn 2009, a group of members from a Faculty of Education began meeting to share their writing and discuss the writing process. We meet regularly and each member takes a turn hosting the meeting. There are no strict deadlines and action items for the meetings; instead, each member takes a turn checking in with the group and asking for feedback or advice on their writing. It is a relaxed and open setting where networking and socializing are as welcome as producing results. The group deliberately set forth to create an environment of non-criticism—we can give feedback but not criticism and we agree to promote support, rather than competition. Through this process, the writing group has served to foster a sense of belonging.
Keywords: wellness; women; academia